A comparative study for evaluating flurbiprofen effectiveness in postoperative pain (International Current Pharmaceutical Journal, 2015)
Aim of the present study was to evaluate the effect of flurbiprofen, which is a member of non-steroidal anti-inflammatory drug group (NSAIDs), on postoperative pain treatment. From September 2013 to May 2014, total of 250 patients were surveyed to perform a systematic evaluation of postoperative pain by comparing flurbiprofen with two other kinds of NSAIDs (diclofenac and ketorolac) and isotonic saline in a double-blind, randomized, placebo-controlled study. Patients were randomized for treatment: 65 cases received flurbiprofen, 60 cases received diclofenac sodium, 60 cases received ketorolac and 65 cases received the placebo (0.9% isotonic saline) (control group). After 24-hours of surgery patients treated with flurbiprofen, ketorolac, and diclofenac showed the lowermost PPI scores compared with those treated with 0.9% isotonic saline (P